2018
DOI: 10.1002/jcb.27462
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA signatures serve as potential diagnostic biomarkers for Helicobacter pylori infection

Abstract: Helicobacter pylor (H pylori), a Gram‐negative, microaerobic human pathogen, has been found to be involved in many gastroduodenal diseases. Accurate diagnosis of H pylori infection is a vital part of the effective management of gastroduodenal diseases. Circulating microRNAs (miRNAs) have shown the potential to be used as noninvasive biomarkers for the diagnosis of infectious diseases. The aim of this study was to explore plasma miRNAs as noninvasive biomarkers for H pylori infection. We performed a plasma miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…A plasma sample also offers the opportunity to detect circulating microRNAs (miRNAs) by molecular techniques. For example, the expression of four miR-28-3p, miR-143-3p, miR-151a-3p and miR-148a-3p were shown to be associated with H. pylori infection [ 117 ].…”
Section: Non-invasive Testsmentioning
confidence: 99%
“…A plasma sample also offers the opportunity to detect circulating microRNAs (miRNAs) by molecular techniques. For example, the expression of four miR-28-3p, miR-143-3p, miR-151a-3p and miR-148a-3p were shown to be associated with H. pylori infection [ 117 ].…”
Section: Non-invasive Testsmentioning
confidence: 99%
“…Thus, these four miRNAs combined may constitute a "specific biomarker signature for H. pylori infection". 39…”
Section: H Pylori Infection Was Introduced By Yu Et Al Using High-tmentioning
confidence: 99%
“…Reports showed that the AUC of miR-28-3p was 0.792 (95% confidence interval: 0.689-0.896), and the high expression of miR-28-3p in plasma could be used as a non-invasive and stable biomarker for detecting pulmonary embolism ( 48 ). Yu et al ( 49 ) used qRT-PCR and then analyzed the operating characteristics of the subjects, and found that the expression of miR-28-3p, miR-143-3p, miR-151a-3p and miR-148a-3p were closely related to Helicobacter pylori infection. The above four plasma miRNA groups were expected to be used as non-invasive biomarkers for Helicobacter pylori infection.…”
Section: Discussionmentioning
confidence: 99%